Nuclear Energy Encyclopedia : Science, Technology, and Applications - Krivit, Steven B., editor 526951; Lehr, Jay H., 1936-, editor 250703; Kingery, Thomas B., editor 526952 (Hoboken, N.J. : Wiley, 2011)
A significant milestone in the history of nuclear technology, Nuclear Energy Encyclopedia: Science, Technology, and Applications is a comprehensive and authoritative reference guide written by a committee of the world's leading energy experts. The encyclopedia is packed with cutting-edge information about where nuclear energy science and technology came from, where they are today, and what the future may hold for this vital technology. Filled with figures, graphs, diagrams, formulas, and photographs, which accompany the short, easily digestible entries, the book is an accessible reference work for anyone with an interest in nuclear energy, and includes coverage of safety and environmental issues that are particularly topical in light of the Fukushima Daiichi incident. A definitive work on all aspects of the world's energy supply, the Nuclear Energy Encyclopedia brings together decades of knowledge about energy sources and technologies ranging from coal and oil, to biofuels and wind, and ultimately nuclear power.